Examining Maladaptive Functioning in Physical Education: A Psychometric Analysis of the Psychological Need Thwarting Scale Among Spanish Secondary Students. Issue 6 (December 2019) - Burgueño, Rafael; Sánchez-Gallardo, Isabel; Macarro-Moreno, José; Lirola, María-Jesús; Medina-Casaubón, Jesús
This research aimed to adapt the Psychological Need Thwarting Scale for use in the Spanish physical education (PE) context and to examine its psychometric properties with secondary school students. Participants were 459 secondary school PE students (206 boys and 253 girls, Mage  = 15.41, SDage  = 1.05). A confirmatory factor analysis supported an 11-item three-factor correlated model that remained invariant across gender and age. Internal consistency analysis showed adequate values for autonomy (α = .79, ρ = .80, average variance extracted [AVE] = .50), competence (α = .85, ρ = .86, AVE = .61), and relatedness (α = .86, ρ = .86, AVE = .68) need frustration. Temporal stability analysis displayed appropriate values for autonomy (intraclass correlation coefficient [ICC] = .81), competence (ICC = .89), and relatedness (ICC = .78) need frustration. Structural equation modeling showed that, while psychological need satisfaction positively predicted autonomous motivation (β = .72, p  < .001), psychological need frustration positively predicted controlled motivation (β = .43, p  < .001) and amotivation (β = .48, p  < .001). The adapted Psychological Need Thwarting Scale was shown to be a valid and reliable measure for assessing psychological need frustration in Spanish secondary school students.